2019
DOI: 10.1021/acs.macromol.9b00745
|View full text |Cite
|
Sign up to set email alerts
|

Polymethylferrocene-Induced Photopolymerization of Cyanoacrylates Using Visible and Near-Infrared Light

Abstract: Metallocene-induced photopolymerization of cyanoacrylates based on electron transfer processes has been proposed as an alternative to more conventional light-curing strategies relying on photobase generators. However, successful application of this methodology has so far only been achieved for very reactive cyanoacrylates under UV illumination and long irradiation times, which eventually hampers its practical use. To overcome these limitations, we describe in this work the use of electron-rich polymethylferroc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 41 publications
0
11
0
Order By: Relevance
“…[216][217] To overcome this drawback, in 2019, this topic was revisited with the development of electron-rich ferrocenes (See Figure 6). [218] Interestingly, the authors demonstrated the possibility to apply this strategy to the polymerization of two cyanoacrylate monomers of interest, namely butyl 2-cyanoacrylate and 2-octyl 2-cyanoacrylate. Indeed, these two monomers can be found in numerous commercial formulations due to their low toxicities and their high viscosities [219].…”
Section: Ferrocene and Alkyl-substituted Ferrocenesmentioning
confidence: 99%
See 2 more Smart Citations
“…[216][217] To overcome this drawback, in 2019, this topic was revisited with the development of electron-rich ferrocenes (See Figure 6). [218] Interestingly, the authors demonstrated the possibility to apply this strategy to the polymerization of two cyanoacrylate monomers of interest, namely butyl 2-cyanoacrylate and 2-octyl 2-cyanoacrylate. Indeed, these two monomers can be found in numerous commercial formulations due to their low toxicities and their high viscosities [219].…”
Section: Ferrocene and Alkyl-substituted Ferrocenesmentioning
confidence: 99%
“…Using these conditions, the polymerization of diEtMM could be ended at 431 s, upon irradiation at 420 nm (I = 46 mW/cm²) (See Figure 8). Reproduced with permission from Faggi et al [218]. Copyright 2019 American Chemical Society.…”
Section: Ferrocene and Alkyl-substituted Ferrocenesmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, photobase generation with ferrocene was revisited in the context of electron-enriched ferrocenes, enabling the polymerization of cyanoacrylates bearing long alkyl chains (See Figure 26). [138] Figure 26. Chemical structures of polymethylferrocenes.…”
Section: Ferrocenementioning
confidence: 99%
“…UV-visible absorption spectra of Me10-Fc in acetonitrile and ethyl 2cyanoacrylate. Adapted with permission from Faggi et al [138]. Copyright 2019 American Chemical Society.…”
Section: Ferrocenementioning
confidence: 99%